2011
DOI: 10.1371/journal.pone.0027622
|View full text |Cite
|
Sign up to set email alerts
|

I-MOVE Multi-Centre Case Control Study 2010-11: Overall and Stratified Estimates of Influenza Vaccine Effectiveness in Europe

Abstract: BackgroundIn the third season of I-MOVE (Influenza Monitoring Vaccine Effectiveness in Europe), we undertook a multicentre case-control study based on sentinel practitioner surveillance networks in eight European Union (EU) member states to estimate 2010/11 influenza vaccine effectiveness (VE) against medically-attended influenza-like illness (ILI) laboratory-confirmed as influenza.MethodsUsing systematic sampling, practitioners swabbed ILI/ARI patients within seven days of symptom onset. We compared influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 17 publications
8
77
6
Order By: Relevance
“…Generalisability to regions with a different profile of vaccine uptake may be limited on that basis. In recent analyses, we [12] and others [29,30,42] have noted a trend toward improved VE with recurrent receipt of the A(H1N1)pdm09 antigen, although other studies have reported contrary findings [28,31,35]. Assessment of these effects may benefit from the additional power available in end-of-season analysis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Generalisability to regions with a different profile of vaccine uptake may be limited on that basis. In recent analyses, we [12] and others [29,30,42] have noted a trend toward improved VE with recurrent receipt of the A(H1N1)pdm09 antigen, although other studies have reported contrary findings [28,31,35]. Assessment of these effects may benefit from the additional power available in end-of-season analysis.…”
Section: Discussionmentioning
confidence: 76%
“…The 2013/14 mid-season VE estimate against influenza A(H1N1)pdm09 of ca 75% is in the upper range of recent seasons' VE estimates for nonadjuvanted TIV against A(H1N1)pdm09 reported since 2010 from Canada [11,12,21], Europe [28][29][30][31][32] and the US [33][34][35], which span ca 60-80%. With several times more influenza A(H1N1)pdm09 cases already contributing thus far in 2013/14 than in previous seasons in Canada, we are likely to converge upon a more stable and accurate estimate of TIV protection against A(H1N1) pdm09 infection this season.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The most recent estimates for TIV efficacy among non-institutionalized elderly are from a large European study, which found a 60% efficacy in those >60 years of age. [218] Limited data from tropical settings have comparable findings: a RCT conducted in Thailand of adults ≥ 60 years living in the community detected a relative risk reduction of ILI of 56% (decreased incidence from 11% to 5% during the study period). [219] Among institutionalized elderly, observational study on estimates of influenza VE in preventing medically-attended acute illness were slightly lower than the Cochrane review estimate, ranging from 20%-40%.…”
Section: Vaccine Performancementioning
confidence: 99%
“…The "cases" and "test-negative controls" both sought care for an influenza-like illness, typically defined as fever plus respiratory symptoms (17,26,(29)(30)(31), and the test-negative controls are those who test negative on the real-time reverse-transcriptase polymerase chain reaction (rRT-PCR) test for influenza virus.…”
Section: Test-negative Designsmentioning
confidence: 99%